LEGAL ANALYSIS OF CONTRADICTIONS IN THE TESTIMONY OF THE WITNESS A DE CHARGE THAT INFLUENCE THE DEFENDANT: A CASE STUDY OF MA DECISION NUMBER 4050 K/PID.SUS/2024 - Sofia Khairunnisa Damanik; Atikah Rahmi (International Journal of Synergy in Law, Criminal, and Justice, 2026)
The defendant's right to present mitigating witnesses (witnesses a de charge) is an integral part of the principle of fair trial and the protection of human rights in criminal procedural law. Normatively, the Criminal Procedure Code (KUHAP) does not differentiate the evidentiary value of witnesses based on the party presenting them, but rather emphasizes the fulfillment of formal and material requirements for witness testimony as valid evidence. However, in criminal justice practice, the testimony of witnesses a de charge is not always mitigating and in certain conditions actually contains contradictions that strengthen the charges and incriminate the defendant. This study aims to analyze the legal position and legal implications of the contradictions in the testimony of witnesses a de charge that incriminate the defendant, with a case study of Supreme Court Decision Number 4050 K/Pid.Sus/2024. The research method used is normative legal research with a statutory, doctrinal, and court decision study approach. The results of the study indicate that the witness's status as a de charge does not determine the direction of the assessment of his testimony. Judges, based on the principle of freedom to negatively assess evidence in the statutory evidentiary system, have the authority to objectively assess the substance, consistency, and relevance of witness testimony. Supreme Court Decision Number 4050 K/Pid.Sus/2024 confirms that contradictory testimony from a de charge witness may still be used as part of the evidence against the defendant as long as it meets the requirements of valid evidence and is linked to other evidence. This finding demonstrates that the protection of the defendant's rights within a fair trial framework is not absolute but must be placed proportionally in the pursuit of material truth and the upholding of substantive justice.